Matrix characterization of symmetry groups of boolean functions - Jasionowski, P. (Algebra and Discrete Mathematics, 2012)
We studies symmetry groups of boolean functions and construct new way of description of this problem in matrices language. Some theorems about constructions of symmetry groups with using matrices are presented. Some properties of this approach are given.